Pengaruh Lokasi dan Kualitas Pelayanan terhadap Kepuasan Pelanggan Toko Sembako Andika pada Pasar Jaya Kramat Jati Jakarta Timur - Muhammad Firdaus Valeri (Global Leadership Organizational Research in Management, 2025)
Andika Grocery Store is a grocery store that sells products in the form of groceries for customer needs. This study aims to analyze the effect of location and service quality on customer satisfaction at Andika Grocery Store located in Pasar Jaya Kramat Jati, East Jakarta. The sample in the study was 40 respondents using saturated sampling techniques, all populations in this study were used as research samples. The data collection technique used a questionnaire method with a Likert scale. Based on the results of this study, the location variable (X1) has a positive and significant effect on customer satisfaction (Y) obtained the results of the calculation of t count> t table (3.394> 1.687) with a significance level of 0.002 <0.05. The service quality variable (X2) has a positive and significant effect on the Customer satisfaction (Y). This is shown from the results of the calculation of t count> t table (3.980> 1.687) with a significance level of 0.001<0.05. Simultaneously, the location variable (X1) and the service quality variable (X2) have a positive and significant influence on customer satisfaction (Y). This is obtained from the results of the F calculation of 32,347 with a significance level of 0.001 <0.05 and Fcount> Ftable (32.347> 3.12). The results of the determination coefficient analysis (R2) obtained R Square of 0.530 or 53.0% influenced by the location variable (X1) and the service quality variable (X2) while the remaining 47.0% (100% -47.0%) is influenced by other independent variables not examined in this study.